Comprehensive manual therapy for the upper extremity the video - Kostopoulos, Dimitrios; Rizopoulos, Konstantine; Slack Incorporated (Thorofare, NJ : SLACK, 2004)
(Producer) Experts apply the latest techniques to effectively treat injuries and ailments to the upper extremity.
Dimitrios Kostopoulos, Konstantine Rizopoulos.
Keywords: Upper Extremity -- injuries; Manipulation, Orthopedic -- methods; Myofascial Pain Syndromes -- therapy